1992
DOI: 10.1111/j.1349-7006.1992.tb00113.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breast Self‐examination on Early Detection and Survival

Abstract: To investigate the effect of breast self‐examination (BSE), we compared the stages, survival, and the risk of death for 355 patients with breast cancer detected by BSE with those for 1,327 patients with breast cancer detected by chance. The early stages of the disease were found to be more common among the symptomatic breast cancer patients detected by BSE than those by chance. The 5‐year overall survival rate was 94.4% for the symptomatic patients detected by BSE, and was significantly higher by 8.7% than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Relative risk of having advanced breast cancer in BSE vs non-BSE groups Practise BSE vs do not practise BSE Foster, 1984Huguley, 1988Kurebayashi, 1994 All All Koibuchi, 1998Kuroishi, 1992Greenwald, 1978Owen, 1985Ogawa, 1987Tamburini, 1981Feldman, 1981Smith, 1985Smith, 1980 Cancer found by BSE vs found by chance 0.60 (0.46 −0.80) 0.66 (0.44 −1.01) Figure 2 Observational studies of women with breast cancer, comparing the rates of advanced breast cancer between the BSE and non-BSE groups. A test for heterogeneity between the studies yielded a P-value of o0.001 for those studies based on women who practise BSE and a P-value of 0.051 for those based on finding cancer by BSE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Relative risk of having advanced breast cancer in BSE vs non-BSE groups Practise BSE vs do not practise BSE Foster, 1984Huguley, 1988Kurebayashi, 1994 All All Koibuchi, 1998Kuroishi, 1992Greenwald, 1978Owen, 1985Ogawa, 1987Tamburini, 1981Feldman, 1981Smith, 1985Smith, 1980 Cancer found by BSE vs found by chance 0.60 (0.46 −0.80) 0.66 (0.44 −1.01) Figure 2 Observational studies of women with breast cancer, comparing the rates of advanced breast cancer between the BSE and non-BSE groups. A test for heterogeneity between the studies yielded a P-value of o0.001 for those studies based on women who practise BSE and a P-value of 0.051 for those based on finding cancer by BSE.…”
Section: Resultsmentioning
confidence: 99%
“…Again there was no strong evidence of heterogeneity between the results (P ¼ 0.26). If the study (Kuroishi et al, 1992) in which some women had mass screening is excluded, the estimate is not much changed the pooled relative risk is 1.00 (95% CI 0.85 -1.18, P ¼ 0.98). Figure 2 shows the relative risk of having advanced breast cancer in women who practise BSE compared to those who did not, among all women newly diagnosed with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that 75-90% of all breast cancers are found by women themselves (7) even though most women do not examine their breasts (13), and BSE is not as sensitive or specific as mammography. Some studies have demonstrated that BSE finds tumors at an earlier stage than those found by chance (14), is an important adjunct to screening mammography for finding interval cancers (15), finds tumors not visible on mammography (16), and reduces breast cancer mortality (17,18), while other studies did not produce evidence that BSE found cancer early (19) or reduced mortality (20,21).…”
Section: O N F L I C T I N G E V I D E N C E R E L a T E D T O B S mentioning
confidence: 98%